METHODS OF USING SPORTS AND WELLNESS TOURISM IN THE SYSTEM OF PHYSICAL EDUCATION OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2024)
Abstract: This article describes the ways of improving the health, functional condition and improving the level of physical fitness of students of a higher educational institution engaged in sports and wellness tourism, using means of physical culture and tourism, Scandinavian walking styles.